2016
DOI: 10.4172/2161-105x.1000375
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein in Stable Cystic Fibrosis: An Additional Indicator of Clinical Disease Activity and Risk of Future Pulmonary Exacerbations

Abstract: IntroductionIn stable adult cystic fibrosis (CF) patients, we assessed the role of baseline high sensitivity C-reactive protein (hs-CRP) on CF clinical variables and frequency of intravenous (IV) treated pulmonary exacerbations (PExs) 1-year post-baseline.MethodsWe recruited 51 clinically stable CF patients from our Adult CF Center. We incorporated collected parameters into Matouk CF clinical score and CF questionnaire-revised quality of life score (QOL). We used the clinical minus complications subscores as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
(34 reference statements)
0
15
1
Order By: Relevance
“…Moreover, absolute or delta CRP showed a smaller (and in case of deltas non-significant) correlation with FEV 1 than HE4. Interestingly, other authors had recently reported that variations of CRP levels could be used as an additional indicator of the overall severity of CF and that this biomarker could even predict pulmonary exacerbations [19]. While there was a strong correlation between HE4 and CRP levels in this study, our observation suggests that HE4 is a more suitable biomarker compared to CRP in this regard.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…Moreover, absolute or delta CRP showed a smaller (and in case of deltas non-significant) correlation with FEV 1 than HE4. Interestingly, other authors had recently reported that variations of CRP levels could be used as an additional indicator of the overall severity of CF and that this biomarker could even predict pulmonary exacerbations [19]. While there was a strong correlation between HE4 and CRP levels in this study, our observation suggests that HE4 is a more suitable biomarker compared to CRP in this regard.…”
Section: Discussioncontrasting
confidence: 45%
“…Currently, there are no unambiguous plasma/serum-based biomarkers for monitoring CFTR modulating therapy efficacy, thus, there is an unmet need to establish a sensitive and easily reproducible biomarker, which is easily performed and accessible, ideally plasma/ serum based. Several laboratory parameters have been investigated in this regard, especially for the prediction of pulmonary exacerbations, such as CRP and interleukin-1β levels in serum and soluble CD14 levels in plasma [19,27]. In addition, metalloproteinases 2 and 9, and IL-8 levels were analyzed in bronchoalveolar lavage samples [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calprotectin does demonstrate some early promise with some ability to predict PEx, but its clinical utility remains unclear [64]. Matouk et al showed that patients with a higher hsCRP were more likely to have more clinically active disease and future PEx [65]. Biomarker panels may prove to be more useful than any single biomarker.…”
Section: Pulmonary Exacerbations (Pex): Diagnosis and Etiologymentioning
confidence: 99%
“…5 High levels of C-reactive protein are associated with lower forced expiratory volume in the first second in individuals with cystic fibrosis. 6 In addition to C-reactive protein levels, the C-reactive protein/albumin ratio can be evaluated and used as an inflammatory-nutritional factor. 7 The systemic inflammatory response is associated with a continuous catabolic response, which exerts an effect on fat-free mass and leads to reduced skeletal muscle mass and wastage of inspiratory muscles.…”
Section: Introductionmentioning
confidence: 99%